2015
DOI: 10.1071/hc15309
|View full text |Cite
|
Sign up to set email alerts
|

Rural health care in New Zealand: the case of Coast to Coast Health Centre, Wellsford, an early Integrated Family Health Centre

Abstract: INTRODUCTION: Primary health care is critical, particularly in rural areas distant from secondary care services. AIM: To describe the development of Coast to Coast Health Centre (CTCHC) at Wellsford, north of Auckland, New Zealand and reflect on its achievements and ongoing challenges. METHODS: Interviews were conducted with staff and management of CTCHC and with other health service providers. Surveys of staff and a sample of enrolled patients were undertaken. Numerical data on service utilisation were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…An evaluation of the Primary Health Care Strategy (2003–2010) reported that GP liaison positions and participation in joint committees resulted in better sharing of information; delivery of specialist services in practices; and up-skilling of GPs to undertake some specialist functions (Raymont and Cumming, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An evaluation of the Primary Health Care Strategy (2003–2010) reported that GP liaison positions and participation in joint committees resulted in better sharing of information; delivery of specialist services in practices; and up-skilling of GPs to undertake some specialist functions (Raymont and Cumming, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Poor relationships between professional groups are a substantial barrier to integrating services at the provider level (Malatest International, 2016). Difficulties in communication with professionals due to separation between general practices were also reported (Raymont and Cumming, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The needs of rural populations may be better met by spreading skills across a wider range of health practitioners in rural health teams. rural integrated family health centres, 30 rural pop-up health clinics, and mobile health buses are examples of innovative models. moreover, a health care workforce that reflects the demographic profile of patients in rural areas may help to overcome other access barriers (eg for rural women and māori).…”
Section: Implications For Practice Policy and Researchmentioning
confidence: 99%
“…Wilkinson reports the findings of research investigating how willing nurses are, in a variety of primary health care workplaces, to accept the independent prescriber role allowed them under recent legislation. 5 Raymont et al report on the organisational enablers and barriers to establishing an integrated family health centre in rural Wellsford, 6 while Döbl et al investigate the potential for social workers to be a core part of primary care teams, 7 and Preston et al report on general practice registrars' interest in providing maternity care. 8 These authors found that there are curious anomalies in the rules surrounding 'community' and 'specialist' prescribing scopes for nurses, 5 that if negotiating the complexities of government contracts can be done, amazing things can be achieved, 6 that funding models limit the full implementation of the Primary Health Care Strategy, 7 and that very few registrars are likely to be interested in providing full maternity care.…”
mentioning
confidence: 99%
“…5 Raymont et al report on the organisational enablers and barriers to establishing an integrated family health centre in rural Wellsford, 6 while Döbl et al investigate the potential for social workers to be a core part of primary care teams, 7 and Preston et al report on general practice registrars' interest in providing maternity care. 8 These authors found that there are curious anomalies in the rules surrounding 'community' and 'specialist' prescribing scopes for nurses, 5 that if negotiating the complexities of government contracts can be done, amazing things can be achieved, 6 that funding models limit the full implementation of the Primary Health Care Strategy, 7 and that very few registrars are likely to be interested in providing full maternity care. 8 Casting a critical eye on the changing face of primary health care in New Zealand as these researchers have is important for the successful evolution of our health system, so it can adequately serve the complex health care needs of our current and future populations.…”
mentioning
confidence: 99%